The Challenge of Teaching Obstetrics to Family Practice Residents - Carroll, June C. (1986)
Physicians who incorporate maternity care into family practice experience an increase in job satisfaction and enjoy a more favourable practice profile. Yet many family physicians are opting out of the obstetrical care of their patients. This development presents a major challenge to the teachers of family medicine. In many teaching programs the response of staff has been to move significant portions of residency training in obstetrics to smaller community hospitals. At Mount Sinai Hospital in Toronto, we believe that an integrated program in the tertiary care centre offers definite advantages. Our obstetrical training program integrates four elements: the community, the hospital, the Department of Family and Community Medicine, and the training program offered by that Department. We expect that family practice residents, by participating in this multifaceted, integrated program, will make a better-informed choice about practising obstetrics.